Management Assessment for Mode I Schools from Northern Educational Region Circuit 6 in 2013 - Torres Sánchez, Ramón (2014)
An management assessment was made of  3 Mode 1 public high schools belonging to the Northern Educational Region Circuit 6 in the Northern Region of Costa Rica in 2013. The general objectives were to assess and propose enhancements to management activities for the high schools participating in the study. The objectives specifically include: 1 – Acknowledging strengths and weaknesses in the schools´curriculum, teaching staff, financial limitations, educational resources and procedures.  2 – Determine the principal management strategies embraced by principals in teh aforementioned instittutions. The study is qualitative.  Findings include: principals overloaded with work, decontexualized content, general lack of motivation among teachers in the workplace and lack of adequate classrooms to provide a quality education